Construction and investigation of plasmid-induced effects on growth of GFP-expressing Salmonella strains - Taraq Naem Zia, Ubaidah Naim; Samynathan, Deepah; Saidi, Hasni Idayu; Selvarajah, Gayathri Thevi; Cheah, Yoke Kqueen (Life Sciences, Medicine and Biomedicine, 2021)
Background: Bacteria such as the Salmonella species had been extensively studied not only for its mechanism of pathogenicity, but for its beneficial utilisation in bacterial-mediated tumour therapy. Genetically modified bacterial strain, BDLA Salmonella Agona (BDLA S. Agona) had shown great promise as tumour targeting and suppressing agent. By, constructing green fluorescent protein (GFP) expressing of this strain, it would be beneficial as it could be used to further study the interaction of the BDLA S. Agona strain with various cancerous cells and the host at the systemic level. However, GFP plasmid-induced strains may exhibit growth defects, and this was investigated in this study. Methods: The GFP-transformed Salmonella strains were constructed, and the replication rate of the strains were investigated using the BacterioScan™ 216R instrument. The replication rate between the strains was compared from the 24-hour data collected and analysed as growth curves. The 24-hour growth curves were constructed using the Log CFU/mL and OD650 data collected by the instrument. Results: It was observed from the growth curves that the transformation of the GFP plasmid into different Salmonella strains did not affect the replication rate of the bacteria. Discussion and Conclusion: This finding answers the objective of the study, and it was concluded that incorporation of the GFP plasmid does not cause any negative effect on bacterial growth. GFP-transformed Salmonella, specifically the BDLA S. Agona strain, could be utilised as a powerful tool for future studies on the mechanism of tumour suppression and real-time in vivo biodistribution of the strain.